Current landscape and future directions of synthetic biology in South America - Gomez-Hinostroza, E. Sebastian; Gurdo, Nicolás; Alvan Vargas, María Victoria Gracia; Nikel, Pablo I.; Guazzaroni, María-Eugenia; Guaman, Linda P.; Castillo Cornejo, David J.; Platero, Raúl; Barba-Ostria, Carlos (Frontiers in Bioengineering and Biotechnology, 2023)
Synthetic biology (SynBio) is a rapidly advancing multidisciplinary field in which South American countries such as Chile, Argentina, and Brazil have made notable contributions and have established leadership positions in the region. In recent years, efforts have strengthened SynBio in the rest of the countries, and although progress is significant, growth has not matched that of the aforementioned countries. Initiatives such as iGEM and TECNOx have introduced students and researchers from various countries to the foundations of SynBio. Several factors have hindered progress in the field, including scarce funding from both public and private sources for synthetic biology projects, an underdeveloped biotech industry, and a lack of policies to promote bio-innovation. However, open science initiatives such as the DIY movement and OSHW have helped to alleviate some of these challenges. Similarly, the abundance of natural resources and biodiversity make South America an attractive location to invest in and develop SynBio projects.